2020
DOI: 10.1089/dia.2020.0034
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Hypoglycemia Awareness Status from Hypoglycemia Experience in Tools for Measuring Impaired Awareness of Hypoglycemia

Abstract: Background: Developing technologies in real-time continuous glucose monitoring (CGM) are successfully reducing severe hypoglycemia (SH) in trials and clinical practice. Their impact on impaired awareness of hypoglycemia, a major risk factor for SH, is uncertain. Methods: The present study examined two scales for assessing hypoglycemia awareness status, the Gold score and the eight-item Minimally Modified Clarke Hypoglycemia Survey (MMCHS), commonly used in trials of CGM, in Portuguese-speaking adults with type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…On the other hand, some of our patients have reported improvements in their perception of hypoglycaemic symptoms after a few days in closed‐loop periods, feelings which faded quickly during the open‐loop periods. It is therefore important to investigate whether hypoglycaemia awareness is durably restored by closed‐loop DBLHU 30 . This would require further explorations with behavioural research, psychoeducational strategies and brain MRI 31,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some of our patients have reported improvements in their perception of hypoglycaemic symptoms after a few days in closed‐loop periods, feelings which faded quickly during the open‐loop periods. It is therefore important to investigate whether hypoglycaemia awareness is durably restored by closed‐loop DBLHU 30 . This would require further explorations with behavioural research, psychoeducational strategies and brain MRI 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to investigate whether hypoglycaemia awareness is durably restored by closed-loop DBLHU. 30 This would require further explorations with behavioural research, psychoeducational strategies and brain MRI. 31,32 Compared with the standard Diabeloop DBLG1 system, 10,11 the DBLHU system allows a higher number of modifications to the command settings, which makes it adaptable to various metabolic phenotypes.…”
Section: Safetymentioning
confidence: 99%
“…Almost all records (11 out of 12) were published between 2016 and 2021 [ 11 , 22 – 31 ]. Of the 12 studies included in this review, only 2 [ 26 , 27 ] investigated SHEs in patients with T1DM. In the remaining studies, three focused on T2DM [ 24 , 25 ] and seven reported data on both T1DM and T2DM [ 11 , 23 , 25 , 28 , 30 – 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each study was conducted in a healthcare setting, although the type of setting varied between studies; emergency hospital setting was the most common [ 24 , 25 , 28 , 30 ], followed by a hospital ward [ 11 , 23 , 29 ], emergency and resuscitation medical vehicle unit [ 31 , 32 ], hospital-based diabetes clinic [ 26 , 27 ] and community pharmacy [ 25 ]. Five studies were based on data collected across multiple centres [ 11 , 23 25 ], with the number of centres ranging from EDs within 7 hospitals [ 24 ] to 233 community pharmacies [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…7 It is less subjective than the Gold score and less well established in the literature, although the association with risk for severe hypoglycaemia is at least as strong. 5 The more complex but very well validated Clarke score measures hypoglycaemia experience as well as awareness status, 10,11 and other scoring systems are used in research. 12,13,14 IAH and its attendant increase in risk for severe hypoglycaemia has been demonstrated to be stressful for partners and family members.…”
Section: Introductionmentioning
confidence: 99%